Proceso de atención de enfermería en adulto mayor con traumatismo craneoencefálico. - Barragán Arguello, Irene Alexandra (2023)
Trauma to the brain is a medical term considered to be an injury to the head area caused by an external blow, which is predictable. It is classified as a global health problem with high mortality rates, depending on its level of severity. In addition, it involves a set of effects on people's living conditions and enormous expenditure for the public health area. The outcome of the clinical case is based on an older adult with head trauma. This pathology involves damage to the brain caused by trauma to the skull. The brain, which together with the spinal cord makes up the Central Nervous System, is protected by the skull and is formed by the cerebrum, the cerebellum and the medulla oblongata. Through this study, we want to highlight that experts in the field of nursing reflect the role of functional elements of health, playing an indispensable role in the proper care of these patients, using methods and attitudes according to the needs that they need. presents each individual.